Pediatric feeding in infants with pierre robin sequence following mandibular distraction osteogenesis - Mabry, Kelly (Perspectives of the ASHA Special Interest Groups, 2016)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-625-935-224-883 tex.type: [object Object]
Keywords: dept.cmd; peer-reviewed

Aphasia, alexia, and agraphia - Purdy, Mary (Reference Module in Neuroscience and Biobehavioral Psychology Encyclopedia of Mental Health (Second Edition), 2016)
Aphasia is a general language disorder resulting from brain damage, and alexia and agraphia are specific impairments in reading and writing, respectively. This article describes the symptoms associated with each disorder, the subtypes of each impairment, and the common causes. Assessment and management approaches consistent with the World Health Organization International Classification of Functioning (WHO-ICF) are briefly reviewed. © 2016 Elsevier Inc. All rights reserved.
10.1016/B978-0-12-397045-9.00056-2 Citation Key: pop00365 Citation Key Alias: lens.org/160-882-999-453-346
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Assessment; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; Management; WHO-ICF; dept.cmd

Intensive multimodal communication treatment for people with chronic aphasia - Purdy, Mary; Wallace, Sarah E. (Aphasiology, 2016)
Background: Clinicians often teach persons with aphasia (PWA) non-verbal strategies to compensate for reduced verbal communication. The manner in which they teach the strategies may have an impact on how well PWA generalise and use the strategies. Previously, multimodal communication treatment (MCT) taught multiple modalities simultaneously. While participants demonstrated some increase in the flexible use of strategies, many communication breakdowns continued to occur. Recent research suggests that intensive treatment protocols result in the greatest increase in skills.Aims: The purpose of this study was to determine whether intensive (2-3hours/day, 5 days/week, for 2 weeks) multimodality communication training for aphasia resulted in increased successful use of verbal and non-verbal communication modalities as well as increased successful communicative repairs during structured communication tasks.Methods & Procedures: Three participants with chronic aphasia completed four baseline sessions, 10 treatment sessions across two phases (i.e., five sessions per phase), and three post-treatment sessions.Outcomes & Results: Two of the three participants demonstrated gains in the acquisition of non-verbal strategies during training and increased use of strategies on a referential communication task.Conclusions: Although MCT delivered intensely resulted in increased use of non-verbal modalities for two out of three participants, the results were similar to that achieved through the use of a non-intensive treatment protocol. Therefore, future research is needed to examine other potential modifications to maximise the gains people with aphasia receive from multimodal interventions.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-825-785-657-129 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Article; Cognitive Linguistic Quick Test; accuracy; adult; aphasia; case report; cognitive function test; communication; dept.cmd; disease severity; hemiparesis; human; intensive treatment; interrater reliability; male; middle aged; multimodality communication training; nonverbal communication; outcome assessment; peer-reviewed; physiotherapy; strategy usage; training